At the origin of modern nursing: Florence Nightingale (1820-1910) versus Ellen Gould White (1827-1915) - Francesco Baldanzi; Donatella Lippi (Infermieristica Journal)
Aim of this short article is to put in light the connections between the similarities and differences between the theories of Florence Nightingale (1820-1910) and those of Ellen Gould White (1827-1915): the first is known around the world because she is considered the founder of modern nursing. Ellen Gould White, on the other hand, is especially familiar within the Seventh-day Adventist Church, of which she was a prominent member. These two women never met or corresponded with one another, yet their writings about health have strong similarities.